2010
DOI: 10.1111/j.1468-2257.2010.00538.x
|View full text |Cite
|
Sign up to set email alerts
|

The Supply of Private Acreage for Public Recreational Use in Southern and Central Appalachia

Abstract: Public lands in Southern and Central Appalachia (SCA) available for outdoor recreational pursuits are limited relative to the rest of the country. This study identifies factors that encourage private landowners to permit public access to their land for recreational purposes and determines how much acreage would be offered in the SCA region. The Tobit and Heckman's sample selection models suggest that the probability of offering land to the public is correlated with the number of acres offered. Having acreage s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…The WMAs are public lands set aside by state agencies primarily for conservation of wildlife habitat and provision of outdoor recreation opportunities to the public. However, these resources are limited in both scope and size and are often in high demand by hunters leading to overuse and issues of conflict (Liu, Pagoulatos, Hu, & Fleming, 2010). Further, existing public lands are under increasing pressure to meet public demand for other types of outdoor recreation including bird 142 N. C. Poudyal et al watching, hiking, and backcountry camping thereby further limiting their potential to serve as primary hunting grounds.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…The WMAs are public lands set aside by state agencies primarily for conservation of wildlife habitat and provision of outdoor recreation opportunities to the public. However, these resources are limited in both scope and size and are often in high demand by hunters leading to overuse and issues of conflict (Liu, Pagoulatos, Hu, & Fleming, 2010). Further, existing public lands are under increasing pressure to meet public demand for other types of outdoor recreation including bird 142 N. C. Poudyal et al watching, hiking, and backcountry camping thereby further limiting their potential to serve as primary hunting grounds.…”
Section: Introductionmentioning
confidence: 95%
“…For example, Liu et al (2010) found that the likelihood of private landowners in the Southern Appalachians offering public access to their land for recreation was positively related to the total supply of acres available. Zhang, Hussain, and Armstrong (2006) and Hussain et al (2007) surveyed non-industrial private forest land owners in Alabama and Mississippi, respectively, to investigate the factors influencing landowners' participation in lease hunting and their expected lease rates.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Land owners have many reasons for which they do not want their land opened to outside use 3 . Land for sale is often indicated as "hunting land," and those who purchase it, despite the significant role they play in wildlife management, may not want outside parties to hunt on their land, despite the benefit that could have to wildlife and natural resource management [1] 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Private owners can potentially increase efficiency through opening land, either pro bono or for a fee, to outside hunters [3]. However, decision strategies of land owners may be biased against opening land to outside use.…”
Section: Introductionmentioning
confidence: 99%